2014
DOI: 10.4049/jimmunol.1301233
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Expression Mapping Identifies a Link between the Complement and Cholinergic Systems in the Rat Central Nervous System

Abstract: The complement system is activated in a wide spectrum of CNS diseases and is suggested to play a role in degenerative phenomena such as elimination of synaptic terminals. Still, little is known of mechanisms regulating complement activation in the CNS. Loss of synaptic terminals in the spinal cord after an experimental nerve injury is increased in the inbred DA strain compared with the PVG strain and is associated with expression of the upstream complement components C1q and C3, in the absence of membrane atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…The genetic link between local expression of BuChE and C3 after experimental nerve injury provided a rationale to determine BuChE activity in the clinical samples [ 19 , 34 ]. In addition, activity of AChE, the other main ACh hydrolyzing enzyme [ 35 ], was determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic link between local expression of BuChE and C3 after experimental nerve injury provided a rationale to determine BuChE activity in the clinical samples [ 19 , 34 ]. In addition, activity of AChE, the other main ACh hydrolyzing enzyme [ 35 ], was determined.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that genetically determined susceptibility to neurodegeneration after a standardized nerve injury among inbred rat strains is associated with a more prominent local inflammatory response with elevated expression of the upstream complement proteins C1q and C3 [ 18 ]. By performing genome-wide expression profiling and linkage analysis in a large inbred rat strain intercross we found co-regulation of complement C3 immediately downstream of butyrylcholinesterase (BuChE), an enzyme that hydrolyses acetylcholine (ACh) [ 19 ]. BuChE has been proposed as a risk gene for sporadic Alzheimer´s disease (AD) [ 20 ] and we recently showed that such patients carrying a BuChE allele coding for a protein with reduced activity displays lower levels of glial activation markers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies linking mRNA levels to the genome in a single tissue include Monti et al (2008), Petretto et al (2008), Pravenec et al (2008), Jirout et al (2010), Low et al (2013) and Thessen Hedreul et al (2013), and across different tissues include Hubner et al (2005) and Langley et al (2013). Gene regulatory networks can also be linked to the genome (exemplified by Lindblom et al, 2014; Saba et al, 2015; Wang et al, 2015). (B) Metabolite levels, or the metabolome, can also be linked to the genome (exemplified by Dumas et al, 2007).…”
Section: Landmark Integrative Genomics Studies In the Ratmentioning
confidence: 99%
“…For instance, Lindblom et al published a study in 2014 (Table 1) in which they performed eQTL mapping in data collected from spinal cord tissue of an F 2 rat intercross (Lindblom et al, 2014). The aim of this work was to better understand the mechanisms regulating complement activation in the central nervous system.…”
Section: Landmark Integrative Genomics Studies In the Ratmentioning
confidence: 99%
See 1 more Smart Citation